INTEGRATING ETHNOSCIENCE INTO SCIENCE LEARNING ASSESSMENT : TOWARD CULTURALLY RESPONSIVE EVALUATION - I Komang Wisnu Budi Wijaya; I Gede Ratnaya; I Gusti Lanang Agung Parwata; I Dewa Ayu Made Budhyani (EDUPROXIMA : Jurnal Ilmiah Pendidikan IPA, 2025)
This study aims to examine the extent of the integration of local wisdom (ethnoscience) in the science learning evaluation instrument. The study conducted in the form of the type of instrument developed, measurement of instrument quality and also the instrument development model used. This study is a Systematic Literature Review (SLR) study using the PRISMA method with the stages of formulating research questions, collecting literature, determining inclusion and exclusion criteria, collecting data from literature that is still in the inclusion criteria, data analysis and data presentation. The literature was excavated from the Google Scholar and eric.ed.gov websites in the period 2015 – 2025. The number of literature that met the inclusion criteria was 12 articles. The results of the study stated that: 1) the integration of local wisdom (ethnoscience) in the science learning evaluation instrument is limited to the form of tests; 2) the measurement of instrument quality carried out in the form of validity, reliability, discrimination and difficulty level tests and 3) the test development model used partly uses the ADDIE development model.